A 13-Year Time-Lagged Description of General Cognitive and Functional Abilities in Older Men: A Cross-Lagged Panel Model. (June 2023) - Martin, Peter; Poon, Leonard W.; Lee, Gina; Obhi, Hardeep K.; Kallianpur, Kalpana J.; Willcox, Bradley; Masaki, Kamal
Objectives: The purpose of this study was to evaluate a cross-lagged panel model of general cognition and functional abilities over 13 years. The goal was to determine whether general cognitive abilities predict or precede functional decline versus functional abilities predicting cognitive decline.Methods: The sample included 3508 men (71–93 years of age at baseline) of the Kuakini Honolulu-Asia Aging Study who were tested repeatedly using a global cognitive test and an assessment of functional capacity. Education and age served as covariates. Cross-lagged models were tested, assessing stationarity of stability and cross-lags.Results: The overall model fit the data well. Cognitive scores had better stability than functional abilities and predicted functional abilities more strongly than functional abilities predicted cognitive scores over time. The strength of all cross-lags increased over time.Discussion: These longitudinal data show that cognitive scores predicted functional decline in a population-based study of older men.